2014
DOI: 10.1007/s10875-014-0087-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Gastrointestinal Viruses and Diminished Secretory Immunoglobulin a Levels in Antibody Deficiencies

Abstract: We here report an increased prevalence of gastrointestinal viruses and gastrointestinal complaints in antibody deficient patients. Patients that tested positive for gastrointestinal viruses showed diminished serum- and secretory IgA levels, and only in patients, virus positivity was associated with signs of mucosal inflammation. These findings suggest that particularly patients with low IgA are at risk for longstanding replication of gastrointestinal viruses, which may eventually result in CVID-related enterop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…This finding strongly suggests that patients with enteropathy exhibit more mucosal immunodeficiency than those without enteropathy and are therefore more at risk for a form of gut infection that could cause enteropathy as extensively discussed below. Prior studies partially support this conclusion in that they showed that CVID patients with relatively low IgA levels were more prone to develop various bacterial and viral infections than other CVID patients [28],[29]. However, these studies did not show that low mucosal IgA levels was associated with enteropathy; this discrepancy may be related to the sensitivity of the staining procedures used in the prior studies as well as the fact that they did not evaluate patients by assessing mucosal Ig mRNA levels (which in this study corroborated the tissue staining findings).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding strongly suggests that patients with enteropathy exhibit more mucosal immunodeficiency than those without enteropathy and are therefore more at risk for a form of gut infection that could cause enteropathy as extensively discussed below. Prior studies partially support this conclusion in that they showed that CVID patients with relatively low IgA levels were more prone to develop various bacterial and viral infections than other CVID patients [28],[29]. However, these studies did not show that low mucosal IgA levels was associated with enteropathy; this discrepancy may be related to the sensitivity of the staining procedures used in the prior studies as well as the fact that they did not evaluate patients by assessing mucosal Ig mRNA levels (which in this study corroborated the tissue staining findings).…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study of infection in CVID patients it was found that sporadic infection with a variety of bacterial and viral pathogens does occur in CVID, but no evidence that these were causative of enteropathy and in most cases the infection did not cause symptomatic disease [33]. A possible exception to this trend is the possibility that CVID is caused by norovirus infection since this organism has been found in stool and biopsies of some (but not all) patients with this condition [29, 33, 34]. Our molecular analysis of organisms associated with the duodenal specimens showed that CVID patients with and without enteropathy exhibited a relatively low norovirus positivity in biopsies (Supplementary Figure S9).…”
Section: Discussionmentioning
confidence: 99%
“…There are certain stable lymphocytes and macrophages in the vagina, which simultaneously serve a role in immune phagocytosis in the invasion of exogenous pathogens, promote cellular immune response and activate humoral immunity; and this forms the first line of defense for preventing the invasion of pathogens (21). IgG is the main antibody in the serum and the extracellular fluid, and may persistently exist in the vaginal local immunity throughout the process of HPV infection (22).…”
Section: Il-mentioning
confidence: 99%
“…This suggests that immune factors may serve an important role in promoting HPV seroconversion in patients in different grades of cervical lesions. A number of studies revealed that when mild inflammation occurred in the genital tract, sIgA secretion increased to remove pathogens (21,24). When inflammation continued to progress and the mucosal epithelial cells and plasma cells were damaged, the defense function was weakened and sIgA secretion was decreased.…”
Section: Il-mentioning
confidence: 99%
“…Recently, Norovirus has been noted as an increasingly important enteric infection in patients with CVID, leading in some cases to severe chronic enteropathy. Notably, Noroviral clearance may be associated with improved histopathological features and resolution of villous atrophy [10] [11]. …”
Section: Infectious Complications Of Cvidmentioning
confidence: 99%